(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
The aim of this study was to examine the problem-posed learning approaches of eighth grade students in the Active Learning framework supported by GeoGebra. Case study was used in this study. The study group comprised 19 eighth grade students. Interview forms, learning activities, unstructured observations and students’ problems posed with GeoGebra software during the intervention were used as data collection tools. Descriptive analysis was used to analyze the data. To investigate students’ skills through the stages of the Active Learning Framework, seven activities were developed and applied for each acquisition in triangles with congruence and similarity sub-learning domains. GeoGebra software was introduced to students for three weeks before the intervention and the process continued for ten weeks. As a result of the analysis of the data, Active Learning Framework supported by GeoGebra software was appeared to be an effective approach in improving the skills of students in this context by transferring the problem solving and posing to the learning environment in a systematic way.